Buddhism under Capitalism - Payne, Richard K. (Bloomsbury Publishing Plc, 2022)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Illustrations -- Acknowledgments -- The Economic Study of Buddhism -- Part I: Historical Perspective -- Chapter 1: Monastic Capitalism? On the Inclusiveness of Tibetan Monastic Institutions -- Part II: Contemporary Studies -- Chapter 2: Selling Buddhism by Branding Mindfulness and Reiki as Valuable, Secular Services: Three Interacting Economic Models -- Chapter 3: Consciousness Raising, False Consciousness, and Freud: Buddhist Traditions in Contemporary Mental Health Economies in the United States -- Chapter 4: Buddhist Technoscapes: Interrogating "Skillful Means" in East Asian Monasteries -- Chapter 5: Perceiving Authenticity: Online Tourism Reviews of Buddhist Tourist Destinations -- Chapter 6: Ethics in Small Business Capitalism of Women Kuan Im Followers in Thailand -- Chapter 7: The Business of Buddhism: Creating Karmic Connections in Ladakh and Europe -- Chapter 8: Gross National Happiness: Capitalism under Buddhism in the Kingdom of Bhutan -- Part III: Theoretical Reflections -- Chapter 9: Drawing Blood: At the Intersection of Knowledge Economies and Buddhist Economies -- Chapter 10: A Part of or Apart from Globalization? The Ambivalent Relationship between Buddhism and Modern Capitalism -- Chapter 11: Prolegomena to a Buddhist(ic) Critique of Capitalism -- Notes -- References -- Contributors -- Index.